Evaluasi Program PPDB Berbasis Zonasi di SMP Negeri 2 Pabelan - Chatarina Sitoresmi Triwiniastuti; Bambang Suteng Sulasmono (Universitas Kristen Satya Wacana, 2020)
The admission of new students (PPDB) is a school agenda that is held every year. The purpose of the study is to evaluate the zoning-based PPDB Program in SMP Negeri 2 Pabelan, Semarang Regency. Program evaluation is done by assessing any discrepancies/gaps between the program standards from the central government and the actual conditions of the PPDB program that occurred in SMP Negeri 2 Pabelan. This type of research is a program evaluation research using Discrepancy Model developed by Malcolm Provus. The Discrepancy Model consists of 5 stages: the design stage, the installation stage, the process stage, the product stage, and the cost-benefit analysis stage. However, this research only used 4 stages, namely the design stage, the installation stage, the process stage, and the product stage. Data collection used in this study were, interview, observation, and documentation. The results showed that the design of the category program was sufficient (conformity score 73.3%), the installation of the good category program (100% suitability score), the process of the good category program (suitability score 92.86%), and the program product category was good (the suitability score 87.5%).